Classroom Management in Improving Student Motivation and Learning Outcomes at SD Negeri 2 Karya Jaya, Mesuji Makmur District - Eka Septianingsih; Syarwani Ahmad; Meilia Rosani (International Journal of Studies in International Education, 2025)
This research aims to analyze classroom management in increasing student motivation and learning outcomes. This research was conducted at SDN 2 Karya Jaya, Mesuji Makmur District in four classes, namely class V A, class V B, class VI A, class VI B. The subjects of this research were teachers of classes V and VI at SDN 2 Karya Jaya, Mesuji Makmur District. The method used in this research is qualitative with a descriptive qualitative type. The data sources used are observation, interviews, documentation, book sources, journals and previous research. The results of class management at SDN 2 Karya Jaya in class V A, class V B, class VI A, class VI B look good. Good classroom management is proven to make students have motivation to learn so that students have learning outcomes above the KKTP. The report card data for students who are already above the KKTP is that in classes V A and VI A there are many students above the KKTP, in classes V B and VI B quite a lot of students are above the KKTP. Obstacles in classroom management in the four classes can be overcome by providing technical guidance for teachers, making classes comfortable for students and using varied learning methods, and reporting any damage to school facilities.